Dynamic change of blood profile in rat models with acute skin injury artificially infected with methicillin-resistant Staphylococcus aureus - Yos Adi Prakoso; Nurul Hidayah; Chylen Setiyo Rini; Kurniasih Kurniasih (Veterinary World, 2021)
Background and Aim: A wound is a common problem for humans and animals. The wound becomes more severe if it is infected by bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA). The wound healing mechanism involves various factors, either in the local tissue or the bloodstream. However, the presentation of infected wound healing regarding its impacts on the dynamic change of blood profile is not clearly understood. This study aimed to explore the impacts of wound creation on the blood profile in rat models with and without being artificially infected by MRSA.